(untitled) (Research, Society and Development, 2021)
The use of a cropping system that provides producers with better land use, higher productivity per unit area, greater diversification in production, and consequently agro-economic advantages, has been the choice of vegetables producers. Therefore, the objective of this work was to evaluate the productive and agro-economic benefits of beet-lettuce intercropping under different equitable amounts of Merremia aegyptia and Calotropis procera biomass (20, 35, 50 and 65 t ha-1 on a dry basis) in different lettuce population densities (150, 200, 250, and 300 thousand plants ha-1), in two cropping years in semi-arid environment. In the cultures and in the intercropping, the production and its components and the agro-economic indexes were evaluated. The maximum production of beet commercial roots in intercropping with lettuce was obtained with a productivity of 33.77 t ha-1 in the amount of 65 t ha-1 of M. aegyptia and C. procera biomass incorporated into the soil and in the lettuce population density of 300 thousand plants per hectare, while the maximum lettuce leaf production was achieved with a productivity of 24.40 t ha-1 in the same combination of green manure amounts and lettuce population densities. The greatest agro-economic advantages of the beet intercropping with lettuce were achieved with a system productivity index (SPI) of 32.97 t ha-1, land equivalent coefficient (LEC) of 0.87 and a monetary equivalence ratio (MER) of 1.55, respectively, in the combination of 65 t ha-1 of M. aegyptia and C. procera biomass with a lettuce population density of 300 thousand plants per hectare.